Relevansi Konsep Hukum Islam dalam Menyikapi Isu-Isu Sosial Kontemporer: Sebuah Tantangan Moderasi Beragama - Ismail, Habib (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2025)
The main question in this article is how the concept of Islamic law can address contemporary social issues such as gender inequality, radicalism, religious pluralism, and the environmental crisis in the context of a modern, multicultural and complex society. The purpose of this study is to explore the relevance of Islamic law in responding to various social challenges through an inclusive and adaptive approach to religious moderation (wasathiyyah). The approach used is a qualitative literature study method, utilizing primary sources such as the Qur'an and hadith as well as secondary sources in the form of scientific journals, fatwas, and works of contemporary scholars. The analysis focuses on the integration of basic principles of Islamic law such as justice ('adl), equality (musawah), tolerance (tasamuh), and balance (tawazun), formulated within the framework of maqashid sharia. The main findings of this article indicate that Islamic law has normative flexibility through the instruments of ijtihad, ijma', and qiyas that allow for adjustment to social change without eliminating the fundamental values of Islamic teachings. Religious moderation plays a crucial role in countering extremism, promoting interfaith harmony, championing gender equality, and strengthening environmental conservation ethics. The implications of this research provide a theoretical and conceptual basis that can be used by policymakers, educators, and Islamic legal practitioners to respond to social issues more relevantly. A limitation of this study lies in the lack of empirical or field data to test the implementation of the concepts studied. Nevertheless, the originality of this research lies in the synthesis of classical fiqh discourse and contemporary social demands within a comprehensive conceptual framework, differing from previous studies that tended to be partial or thematic.